Crescentic transformation in primary membranous glomerulonephritis. Issue 788 (June 1991) - Kwan, J. T.; Moore, R. H.; Dodd, S. M.; Cunningham, J.
Abstract : A 31 year old man first developed steroid-resistant idiopathic membranous glomerulonephritis in 1981. Stable normal renal function was maintained until August 1988 when he suffered a clinical relapse with heavy proteinuria and declining renal function. Immunosuppressive therapy with prednisolone and cyclophosphamide was instituted in an attempt to arrest this relapse. Despite this, he later developed acute renal failure with histological evidence of crescentic transformation of his nephritis. This unusual transformation was not associated with features of systemic vasculitis or positive anti-glomerular basement membrane and anti-neutrophil cytoplasmic antibodies.